Development of web-based administration system for Mandeh Pasir Fisherman Group, Marunggi Village, Pariaman City - Januardi Nasir; Yasha Langitta Setiawan; Rio Rahmat Yusran (Journal of Community Service and Empowerment, 2022)
As an area close to the sea, the life of the people of Kota Pariaman is highly dependent on marine products. One of the villages in Pariaman City that is very dependent on marine products is the community of Pasir Marunggi Village, South Pariaman District. The strategic location of Pasir Marunggi village, namely the road to go to the Minangkabau international airport and to Pariaman City, automatically makes this village a frequent stopover, especially with the sek rice stalls in Pasir village, which have characteristics with those around Pariaman. Some of the obstacles faced in addition to the lack of knowledge in the field of Information Technology in the process of promoting aquaculture and catches by fishermen, resulting in a decrease in sales turnover for fishermen.  This community service was aimed to web-based administration system for Mandeh Pasir Fisherman Group, Marunggi Village, Pariaman City. The computer-based administration system is given because there are still many fishermen who are members of the Mandeh - Fisherman Group who do not understand how to manage a computer-based administration system. The expected result is that business groups can do bookkeeping with a computer by introducing Microsoft Word and Excel for administrative facilities and adding block making training to facilitate the promotion of business groups so that they can be known in other areas and increase revenue turnover.